An artificial intelligence approach for biomass devolatilisation in an industrial CFD model with advanced turbulence-chemistry interaction - Du Toit, Philip C. (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.